1978
DOI: 10.1108/eum0000000004993
|View full text |Cite
|
Sign up to set email alerts
|

Channels of Distribution Conceptualisation: A State‐of‐the Art Review

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 43 publications
0
43
0
1
Order By: Relevance
“…Even though this concept is important, very few studies have analysed cooperation exhaustively, instead, choosing to concentrate on the conflict and power aspects. Skinner et al (1992) indicated that most of this type of research tries to project cooperation as a form of level of satisfaction (Anderson and Narus 1990) or the reverse of conflict (Gattorna 1978). Some authors consider cooperation and conflict as the opposite poles of the same concept, which is really an error of typology: they are in fact distinct concepts according to Anderson and Narus (1984) issuing directly out of the nature of interdependence of the parties involved, and they can coexist within the same relationship.…”
Section: Cooperation and Conflictmentioning
confidence: 96%
“…Even though this concept is important, very few studies have analysed cooperation exhaustively, instead, choosing to concentrate on the conflict and power aspects. Skinner et al (1992) indicated that most of this type of research tries to project cooperation as a form of level of satisfaction (Anderson and Narus 1990) or the reverse of conflict (Gattorna 1978). Some authors consider cooperation and conflict as the opposite poles of the same concept, which is really an error of typology: they are in fact distinct concepts according to Anderson and Narus (1984) issuing directly out of the nature of interdependence of the parties involved, and they can coexist within the same relationship.…”
Section: Cooperation and Conflictmentioning
confidence: 96%
“…Early research on marketing channels derived predominantly from work in economics (Coase 1937), which views channels of distribution as flows of goods or services. Research in the early twentieth century tended to regard interactions between firms as optimization or cost minimization problems and vertical marketing systems as extensions of the firm; other, non-economic factors largely were ignored (Gattorna 1978). Mid-century work specific to marketing channels was more prescriptive, designing management decision models that accounted simultaneously for cost functions, revenue opportunities, and information, despite the difficulty of measuring real situations (Bucklin 1966).…”
Section: Pre-1980mentioning
confidence: 99%
“…Marketing channels have been studied using different theoretical frameworks, which we group parsimoniously into two major schools of thought in Table 1 (Gattorna 1978;Stern and Reve 1980). Economics-based, theoretical approaches tend to emphasize economic efficiency or functional optimization as means to reconcile situational constraints and costs through channel design, as well as profits.…”
Section: Perspective 1: Marketing Channel Theories and Constructsmentioning
confidence: 99%
“…In our view, this concept seems very important to us since continuous research has not analyzed it in depth, preferring to study conflict or power. Skinner et al (1992) seem to say that many research studies present cooperation as a form of satisfaction (Anderson et Narus 1990) or as the inverse of conflict (Gattorna 1978). Some authors consider cooperation and conflict as the two inverted poles of the same concept, which can be considered an identification error.…”
Section: Cooperation and Conflictmentioning
confidence: 96%